(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Halophytic plant communities of the Russia coast of the Sea of Azov are described using the Braun-Blanquet approach for the first time. Three variants of the ass. Salicornietum prostratae, new subass. Salicornio perennantis-Suaedetum salsae halimionetosum (class Thero-Salicornietea) and ass. Salicornio prostratae-Halocnemetum strobilaceae (class Salicornietea fruticosae) are established. The name of ass. Salicornio-Halocnemetum Korzhenevsky et Kljukin in Korzhenevsky 2000 is corrected in accordance with the rules of the International Code of Phytosociological Nomenclature.